Most responsible and decisive participation in the Colombian transitional justice (2022)
Most responsible and decisive participation are two legal categories of great current relevance in Colombian transitional justice. These are concepts incorporated into the Constitution thanks to two constitutional amendments that have specified aspects that should guide the justice in this area. Despite their importance, the doctrinal and jurisprudential development of these normative provisions has been very limited, especially with regard to the recently created concept of decisive participation. In this sense, the purpose of this article is to review the normative and case law on both legal categories in order to determine their origins, scope, convergences and divergences and, to propose some approaches to their practical use in the Special Jurisdiction for Peace.